Profits and losses from changes in fair value, executive cash compensation and managerial power: Evidence from A-share listed companies in China - Ruiqing Shao; Chunhua Chen; Xiangzu Mao (China Journal of Accounting Research, 2012)
According to optimal contracting theory, compensation contracts are effective in solving the agency problem between stockholders and managers. Executive compensation is naturally related to firm performance. However, contracts are not always perfect. Managers may exert influence on the formulation and implementation of compensation contracts by means of their managerial power. As fair value has been introduced into the new accounting standards in China, new concerns have arisen over the relationship between profits and losses from changes in fair value (CFV) and levels of executive compensation. In this study, we find that executive compensation is significantly related to CFV. However, this sensitivity is asymmetric in that increases to compensation due to profits from changes in fair value (PCFV) are higher than reductions to compensation due to losses from changes in fair value (LCFV). Furthermore, we find that managerial power determines the strength of this asymmetry.
Keywords: G34; J30; M48; 650; Profits and losses from changes in fair value; Executive compensation; Managerial power